A new active compound from Centaurea species - (:unkn) unknown (Verlag der Zeitschrift fur Naturforschung, 2006)
The extract containing sesquiterpene lactones of Centaurea iberica (Asteraceae) isolated was separated and a steroidal compound, which is stigmast-1,5-dien-β-ol, was purified. The chemical structure was established based on spectroscopic data (UV, IR, MS, 1H NMR, 13C NMR). Both the extract and the compound showed significant antioxidant and antimicrobial activities. © 2006 Verlag der Zeitschrift für Naturforschung.
Keywords: Antimicrobial; Centaurea; Stigmast-1,5-dien-3β-ol